Potential use of movies as teaching tool in English language classroom to encourage active participation and critical thinking / Agelyia A/P Murugan and Wan Noorli Razali - Murugan, Agelyia; Razali, Wan Noorli (2011)
Original Title as Proposed: Potential Use of Film as Teaching Tool in English Language Classroom to Encourage Active Participation and Critical Thinking Original Objectives as Proposed: To identify the potential use of film in encouraging active participation in English language classroom. To identify the potential use of film in encouraging critical thinking in English language classroom. Enhanced Research Title: Potential Use of Movies as Teaching Tool in English Language Classroom to Encourage Active Participation and Critical Thinking